Changing trends in quality of media reporting of suicide in the community following a celebrity suicide in India. (January 2022) - Menon, Vikas; Kar, Sujita Kumar; Ransing, Ramdas; Sharma, Ginni; Pattnaik, Jigyansa Ipsita; Kaliamoorthy, Charanya; Varadharajan, Natarajan; Mukherjee, Srijeeta; Agrawal, Aditya; Padhy, Susanta Kumar; Arafat, SM Yasir
Objective: Little is known about changes in quality of media reporting of suicide in the community following a celebrity suicide. Our objective was to compare trends in quality of media reporting of suicide, before and after the suicide of an Indian entertainment celebrity, against the World Health Organization suicide reporting guidelines. Method: Online news portals of English and local language newspapers, as well as television channels, were searched to identify relevant suicide-related news articles. Comparison of reporting characteristics before and after the celebrity suicide was performed using chi-square test or Fisher's exact test. Results: A total of 3867 eligible news reports were retrieved. There was a significant increase in harmful reporting characteristics, such as reporting the name, age and gender of the deceased ( p  < 0.001 for all comparisons), mentioning the location ( p  < 0.001) and reason for suicide ( p  = 0.04) and including photos of the deceased ( p  = 0.002) following the celebrity suicide. Helpful reporting practices were less affected; there was a significant rise in inclusion of expert opinion ( p  = 0.04) and mention of suicide-related warning signs ( p  = 0.02). Conclusion: Following a celebrity suicide, significant changes in the quality of media reporting of suicide were noted with an increase in several potentially harmful reporting characteristics.